A Female Leaders in the Perspective of Islamic Law and Legal Regulations - Sutrisno, Edy; Fanani, Ahmad; Marsidi, Marsidi; Muhammad, Adamu Abubakar (MILRev: Metro Islamic Law Review, 2023)
The leader is a profession with the functions and duties of representing the government in recording and supervising marriages. Then how women become penghulu seen from Islamic law and legislation. This writing uses library research method with a qualitative descriptive approach. The results of this discussion state; First, from a juridical-normative perspective, if women are appointed as penghulu, their position will be questioned if they carry out their duties as guardian judges, which in fiqh must be a man. Second, it is considered that there are still problems in entering the public sphere for women, such as supervising and recording marriages in the mosque while she is in an impure condition, and attending marriage contracts which are carried out outside the office and outside working hours. Then in PMA Number 20 of 2019 concerning Marriage Registration, it has been explained that the leader can be held by both men and women. Likewise, in the Minister of Administrative Affairs Regulation Number 9 of 2019 concerning the Functional Position of Penghulu, it also does not require that the Penghulu must be held by a male Penghulu.